مناهج تعليم اللغة العربية للناطقين بلغات أخرى - Mochamad Hasyim (Universitas Yudharta Pasuruan, 2017)
Arabic has officially become the sixth world language with English, French, Spanish, Russian and Chinese, with the recognition of the United Nations and many international organizations that they have realized the role of the Arabic language in the dissemination and preservation of human civilization. It is in this context that there has been a great deal of interest in the dissemination of Arabic to non-speakers around the world. And opened a number of scientific institutions and institutes play an important role in this area, and specialists in the development of curricula and teaching materials and methods of teaching Arabic to non-children. In this matter, the language should determine their goals, plans, curricula and teaching methods. These things differ when teaching Arabic to their children and non-speakers. In addition, this research includes the concept of curriculum, the types of curricula for teaching Arabic to its children and speakers in other languages, in addition to the types of curricula for learning the language as a second language and the budget in that.